Study on the Energy-Regeneration-based Velocity Control of the Hydraulic-Hybrid Vehicle - SONG Yunpu (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
This paper simplifies the energy regenerationbased vehicle velocity system of the hydraulichybrid businto a process in which the extension rod of the hydraulic cylinder drives the secondary-element variable delivery pump/motor to change its displacement. This process enables braking of the vehicle and also allows recovery of energy. The stability, energy efficiency and other characteristics of the system are studied based on analysis of mathematical models of the vehicle velocity control. The relevant controller is designed to study effects of the controller on system characteristics. The vehicle velocity control module of the energy regeneration system is stable and able to recovery the inertia energy generated in vehicle braking. After the controller intended to improve response speed is added, system response becomes quicker but energy recovery rate declines. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1565